Moderasi dan Komunikasi antar Tokoh Agama dalam menghadapi pemilu 2024 di Kabupaten Jember - Farawansa, Hisien Khofiah (Icon: Islamic Communication and Contemporary Media Studies, 2023)
Religious figures are people who have contributed to maintaining the smooth implementation of elections in a peaceful manner, namely as a unifier of the people not as a breaker of unity between people. The focus of this research is 1) What is the attitude of religious leaders towards communication and moderation in facing the potential for conflict in the run-up to the 2024 election among the people of Jember. 2) How are the efforts of religious leaders in dealing with the potential for conflict in the 2024 elections. 3) How is the communication pattern between religious leaders in reducing the potential for conflict ahead of the 2024 election. This research uses qualitative research methods that seek to find detailed data with data collection techniques obtained from interviews with religious leaders, observation and documentation. The results of this study led to a conclusion that religious leaders must be neutral, namely by being moderate because by applying a moderate attitude, religious leaders can become mediators when their people experience conflict, by providing enlightenment, tausiyah, and giving appeals as an effort to keep the elections running peacefully, with communication patterns carried out verbally or words.